Family correlates of adolescent volunteerism - Lalap, Belinda A.; Dy, Marison R. (2015)
This study aimed to identify the correlation between family characteristics and adolescent's motivations for volunteering. Fifty student volunteers of University of the Philippines Los Baños ugnayan ng Pahinungod, 16 to 21 years old, were provided with structured self-administered pre-tested questionnaires. Descriptive analysis was used to describe respondent and family characteristics. Spearman correlation test analysis was used to determine the relationship between family attributes and various motivations for volunteering (self-esteem, reciprocity, reactivity, understanding of self and others, and career development). however, for variables whose correlations cannot be computed, cross tabulations were performed. The correlations between variables produced negative and positive directions that point to some influential family variables to volunteering motivations of the adolescents. Parental educational attainment was weakly but positively related to motivation of understanding the self and others. Family income was weakly but positively related to understanding of self and others but negatively and moderately related to reactivity. More volunteers whose parents had occupations had high levels of motivation to volunteer in relation to self-esteem, reciprocity, reactivity, understanding the self and others, and career development. non-involvement by parents in organizations was related with higher motivation to volunteer in relation to self-esteem, reciprocity, reactivity, understanding the self and others, and career development. families, especially the parents, are often the paths by which adolescents are exposed to volunteerism and continue volunteering. Homogeneous responses were observed among the respondents due to the small sample size and limited respondents and their families from various communities to gather more diverse responses on family characteristics influential to volunteerism.
Keywords: Voluntarism; Families and economics; Student volunteers in social service